Systematic Literature Review Sistem Pengendalian Intern Pemerintah dalam Pencegahan Fraud - Kusuma Natita, Rendi; Setiawan, Amelia; Djajadikerta, Hamfri (LP2M Universitas Perjuangan Tasikmalaya, 2024)
This research discusses the government's internal control system in fraud prevention. The study shows that the implementation of SPIP (Government Internal Control System) can minimize fraudulent activities and enhance accountability in fund management. The research method used is a Systematic Literature Review focusing on scientific publications related to the topic. The research steps include database identification, keyword selection, article search, selection based on title and abstract, quality evaluation, and data storage. This research provides important insights for practitioners and researchers in efforts to prevent fraud in fund and asset management. The government's internal control system plays a crucial role in preventing fraud in the public sector. Weaknesses in the government's internal control system include resource limitations, conflicts of interest, and lack of commitment from leadership. The impact of fraud in government includes financial losses, decreased public trust, hindered development, negative influence on decision-making, and legal and investigation costs. Effective SPIP implementation and high organizational commitment are essential in preventing fraud. Recommendations for strengthening SPIP include training, professional certification, strengthening internal control systems, information technology, enhancing morality and ethics, strengthening whistleblowing, leadership support, and leadership oversight.